SUBSTANTIATION OF THE ROLE OF INTELLECTUAL PROPERTY IN CREATING COMPETITIVE ADVANTAGES IN THE INTERNATIONAL MARKET - Plavčan, Peter (Journal of Strategic Economic Research, 2022)
The article highlights the specifics and key role of intellectual property in creating competitive advantages at the macro and macro levels. It is determined that in the conditions of internationalization of trade and economic activity intellectual property is an effective tool for solving many economic problems and, above all, obtaining significant competitive advantages. The analysis of the role of intellectual property in the formation of micro- and macro-level competitive advantages of international economic entities allowed us to explore the mechanisms of production, technological, financial, marketing and organizational-administrative advantages and reveal their essence. Based on the results of the study, modern processes of internationalization of intellectual property are substantiated, it is determined that the globalization of economic activity is accompanied by the growth of international cooperation in intellectual property protection as the only means of creating favorable conditions for intellectual activity. The study uses the following methods: historical and logical to study and analyze the essence of changes in the concept of intellectual property depending on the level of socio-economic development of society and in studying the impact of internationalization of trade and economic relations on international cooperation in regulating intellectual property rights); system analysis for the study of global factors in the formation of the modern concept of intellectual property; analysis and synthesis to study the role of intellectual property in the formation of micro- and macro-level competitive advantages of international economic entities in domestic and foreign markets.